At the poles across kingdoms: phosphoinositides and polar tip growth - Till Ischebeck; Stephan Seiler; Ingo Heilmann (2009)
Phosphoinositides (PIs) are minor, but essential phospholipid constituents of eukaryotic membranes, and are involved in the regulation of various physiological processes. Recent genetic and cell biological advances indicate that PIs play important roles in the control of polar tip growth in plant cells. In root hairs and pollen tubes, PIs control directional membrane trafficking required for the delivery of cell wall material and membrane area to the growing tip. So far, the exact mechanisms by which PIs control polarity and tip growth are unresolved. However, data gained from the analysis of plant, fungal and animal systems implicate PIs in the control of cytoskeletal dynamics, ion channel activity as well as vesicle trafficking. The present review aims at giving an overview of PI roles in eukaryotic cells with a special focus on functions pertaining to the control of cell polarity. Comparative screening of plant and fungal genomes suggests diversification of the PI system with increasing organismic complexity. The evolutionary conservation of the PI system among eukaryotic cells suggests a role for PIs in tip growing cells in models where PIs so far have not been a focus of attention, such as fungal hyphae.